"Tjednik bjelovarsko-križevački" (weekly journal): the importance of periodicals for the research in local history (Libellarium: journal for research in the field of information and related sciences, 2009)
The history of printing and book publication in Bjelovar-Bilogorje District has not been sufficiently studied and evaluated. The few published papers on this topic represent only a scant review of the matter and provide no explanation as to the role of the periodicals, in particular journals and newspapers, in the overall development of the town of Bjelovar and the District.It strikes one as particularly odd how little writing has been devoted to the first Bjelovar weekly newspaper, Tjednik bjelovarsko-križevački.Our paper is an overview of the facts on the beginning of its publication, the makeup of the editorial board and the editors in chief, the contents, genres, columns, circulation, distribution, popularisation and layout. The range of topics covered, the overall atmosphere and the wide scope of the social life covered by the newspaper shed light on its influence on the development of literacy and the culture of reading, and on its role in the cultural, educational and political life of the town and the region in the late 19th and early 20th century.A special reason for writing this text resides in the fact that in the absence of other source material Tjednik bjelovarsko-križevački is an important tool in the study of the local history.The chief study sources were the complete annual editions of Tjednik stored in the National University Library. Bibliographic sources and material were consulted regarding the development of printing and the publication of periodicals. The theoretical starting points were found in the works of Josip Horvat, Božidar Novak, Srećko Lipovčan, Ivanka Kuić, Ivo Perić, Vjekoslav Maštrović and others.The paper utilises the historic and comparative methods, and the methods of compilation, description, analysis and synthesis.The first regionally distributed weeklies were commonly published by local printers with businesses set up in the district centres. An enormous breakthrough in the development of publishing and printing in Bjelovar was made by Adolf Kolesar whose printing outfit opened in 1885. Soon after the outfit opened for business, he started publishing the first newspaper bearing the title Tjednik bjelovarsko-križevački: newspaper for education, economy, social and public life. The first issue came out 1 November 1890, marking the beginning of the development of periodicals in Bjelovar and the District. Adolf Kolesar furnished the technical base for the onset of newspaper publishing in Bjelovar, but the major creators of the content of Tjednik were the long-standing members of the editorial board and reputed columnists, Professor Gustav Fleischer, and solicitor and politician Milan Rojc. Literature, so far published on this matter, stresses that Tjednik ranked among the best regional papers of its time.The paper started out by publishing only the news, curios, items of educational and didactic content, reviews, short stories, sports news and advertisements. Its ambition was to cover matters of interest and reach the readers of the entire Bjelovar-Križevci District, but it had no particular political ambitions.In 1907 the owner and the editorial board changed and the paper became a political bulletin for the Croatian-Serbian coalition, with greater emphasis on the state, political, communal, social and economic matters, important in the life of the District. The last issue came out 30 August 1919, after which date the name was changed to Demokratski glas and the publication became the bulletin for the Yugoslav Democratic Party. In 1924 the paper resumed the old name, Tjednik, but survived only a short time.The research for this paper was greatly impeded by a scantiness of sources, as there are only very few copies of Tjednik preserved in the State Archives and the Bjelovar Town Museum, whereas the Petar Preradović Library in Bjelovar does not own a single copy. Furthermore, there was the matter of reliability of the information found in literature, as it is sometimes incomplete or only partially accurate.The article aims to shed some light on the social and political role of Tjednik and on its information and communication aspects. The study of the contents of Tjednik provided in this article hopes to facilitate further research in the history of the town and the District.
Keywords: Tjednik bjelovarsko-križevački; Bjelovar; Bjelovar-Bilogora District; periodicals